Characteristics of BSCF–SDCC–Ag composite cathode powder for low-temperature solid oxide fuel cell - Yusop, Umira Asyikin; Osman, Muhammad Nur Fikri; Jaidi, Zolhafizi; Azmi, Mohd Azham; Ismail, Azzura; Mahzan, Shahruddin; Tan, Kang Huai; Abd. Rahman, Hamimah (2024)
. A fuel cell is a type of clean energy that may be utilised in various applications across numerous sectors. Solid oxide fuel cell (SOFC) has attracted considerable interest as a fuel cell type due to its excellent efficiency and durability. However, SOFC may encounter specific challenges because of its operating temperature, which is generally high. This circumstance might negatively affect the overall system performance. New materials that can work with SOFCs in the lowtemperature range (LT-SOFC) must be introduced to overcome the challenges. The milled barium strontium cobalt ferrite– samarium-doped ceria carbonate (BSCF-SDCC) composite cathode was introduced as a potential candidate for LT-SOFC material. Argentum (Ag) was added to the BSCF–SDCC composite cathode to act as a catalyst material for efficient performance. The characterisation of a BSCF–SDCC–Ag composite cathode was investigated under two properties, namely, chemical and physical. The X-ray diffraction results for phase identification showed that Ag addition exhibited compatibility with BSCF–SDCC composite cathode with no occurrence of impurities. The morphology and element observation showed that the composite cathode powder was well mixed, and all significant elements were uniformly and homogeneously distributed. The average percentage of porosity value was also obtained in the acceptable range (20%– 40%). Specifically, it ranged from 21.12% to 22.50%. Therefore, the findings of this study prove that the addition of Ag can improve the performance of the BSCF–SDCC composite cathode, which is in line with the function of Ag as a catalyst material